2022
DOI: 10.1186/s13058-022-01504-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA IPW inhibits growth of ductal carcinoma in situ by downregulating ID2 through miR-29c

Abstract: Background Ductal carcinoma in situ (DCIS) of breast is the noninvasive lesion that has propensity to progress to the malignant form. At present, it is still unknown which lesions can potentially progress to invasive forms. In this study, we aimed to identify key lncRNAs involved in DCIS growth. Methods We employ disease-related lncProfiler array to identify IPW in specimens of DCIS and matching control samples and validate the observations in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…In VP64 dCas9 VP64 ΔPWS iPSCs, 8 genes outside the PWS locus showed significant differential expression, although the changes were lower than any PWS genes (Figure 2D). It is possible that these expression changes outside the PWS locus are consequences of upregulation of PWS genes, as several PWS lncRNAs, including IPW in particular, are known to regulate the expression of other genes in trans (Deshpande et al, 2022, Stelzer et al, 2014, Sledziowska et al, 2023). However, we were unable to find any reported evidence that IPW or other PWS lncRNAs regulate these differentially expressed genes.…”
Section: Resultsmentioning
confidence: 99%
“…In VP64 dCas9 VP64 ΔPWS iPSCs, 8 genes outside the PWS locus showed significant differential expression, although the changes were lower than any PWS genes (Figure 2D). It is possible that these expression changes outside the PWS locus are consequences of upregulation of PWS genes, as several PWS lncRNAs, including IPW in particular, are known to regulate the expression of other genes in trans (Deshpande et al, 2022, Stelzer et al, 2014, Sledziowska et al, 2023). However, we were unable to find any reported evidence that IPW or other PWS lncRNAs regulate these differentially expressed genes.…”
Section: Resultsmentioning
confidence: 99%
“…Evidences have demonstrated that miR-29c was involved in cancer progression (Deshpande et al 2022 ; Nai et al 2022 ; Li et al 2021 ; Hozaka et al 2021 ), including NSCLC. For instance, Liu J et al found that upregulation of miR-29c-3p suppressed CDCA4 expression and decreased cell proliferation, migration, invasion, apoptosis, and EMT of melanoma, which hindering melanoma progression (Liu et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidences have illustrated that lncRNAs have significant functions in a wide variety of diseases (Han and Zhang 2022 ; Hou et al 2021 ; Wang et al 2020 ), especially cancer. They were abnormally expressed and exerted huge impact on the aggressive properties through acting as pro-oncogenic or anti-oncogenic roles (Liu et al 2022 ; Zhang et al 2022b ; Deshpande et al 2022 ; Zhou et al 2021 ). For instance, Liao et al ( 2022 ) found that LNMAS suppressed the metastasis of cervical cancer through the interaction with HMGB1 and abrogated the chromatin accessibility of TWIST1 and STC1.…”
Section: Introductionmentioning
confidence: 99%
“…For miRNA, evidence suggests that lncRNAs may act as competing endogenous RNA through which miRNAs are deprived of regulating the downstream target. 3 , 4 In addition, lncRNAs are shown to alter the transcription factor accessibility through chromatin modification and thereby regulating the expression of downstream effectors. 5 Because of this, it is necessary to uncover the regulatory aspects of lncRNAs and circRNAs to undertake better therapeutic measures.…”
mentioning
confidence: 99%
“…For instance, lncRNA IPW is shown to potentiate the DCIS progression to invasive ductal carcinoma (IDC) by ID2 though miR29c. 3 It is therefore essential to decode the functional module of how lncRNA affects the stem cell component for improved translational impact.…”
mentioning
confidence: 99%